Case Study of the Characteristics and Mechanism of Rock Burst near Fault in Yima Coalfield, China - Zhenhua Jiao; Qiupeng Yuan; Peng Zou; Benjun Shi (Shock and Vibration)
Deep mining near faults may easily cause rock bursts, which seriously threaten mining safety. Based on the engineering background of deep mining near fault in Yima coalfield, by collecting the rock burst events that happened near fault during deep mining, the correlation between fault structure and time-space features of rock burst was analyzed. The results show that the deep rock burst accounts for 84% in Yima coalfield at 600 m and 93% in the mining area within 1000 m from F16 fault. The risk of rock burst is positively correlated with mining depth and negatively correlated with the distance between mining area and F16 fault, and the frequency and intensity of rock burst near F16 fault increase significantly. Rock burst occurs in high stress concentration area, mainly in roadway, releasing energy level of 1.1 × 104 J–3.5 × 108 J, with impact damage range of 60–500 m. The mechanism of rock burst was explained from the view of the distribution of mining stress in surrounding rock. The stress of coal seam in deep mining near fault increases, and the disturbance effect of fault is obvious. Rock burst is easy to be induced under static and dynamic loads. The occurrence and mechanical characteristics of fault have different effects on rock burst and should be considered when evaluating the risk of rock burst.